2019
DOI: 10.5114/ms.2019.91247
|View full text |Cite
|
Sign up to set email alerts
|

Stress and coping strategies of medical students during their first clinical practice – a pilot study

Abstract: Introduction: The medical profession is acknowledged as one of the most stressful. The time devoted to acquire knowledge and practical skills is a source of stress for students, but also an opportunity to learn how to deal with it. Aim of the research: To assess how medical students deal with stress during their first clinical practice. Material and methods: The study was conducted in a group of 526 students of: nursing, physiotherapy, medical rescue, and obstetrics at a university. The research tools included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
4
14
0
Order By: Relevance
“…More than half of the students in the presented study felt stress of high intensity. Similar results were obtained by other researchers [ 8 , 9 , 16 , 41 ]. Students undertake differentiated strategies of coping with stress in difficult situations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More than half of the students in the presented study felt stress of high intensity. Similar results were obtained by other researchers [ 8 , 9 , 16 , 41 ]. Students undertake differentiated strategies of coping with stress in difficult situations.…”
Section: Discussionsupporting
confidence: 92%
“…Nursing students deal with various difficult situations, especially during practical classes in health care facilities [3]. Many studies have confirmed the occurrence of such stressful situations [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Stress in today's world is an integral part of life. This term can be used to describe not only sudden, traumatic experiences, but also the constant difficulties and changes that happen in life that are just part of living; the majority of society encounters and situations that cause stress on a daily basis and affect overall well-being (Bodys-Cupak et al, 2016, 2019aKowalczuk et al, 2017;Kwak et al, 2018;Mukhtar, 2020;Nwachukwu et al, 2020). Seyle (1977) believed that no person in his life was able to free himself from stress.…”
Section: Introductionmentioning
confidence: 99%
“…In the concept of life changes, the environment in which the person experiences stress plays a significant role. Nursing students exhibit a variety of stress coping strategies, from active to avoidance (Bodys-Cupak et al, 2016, 2019aMcCarthy et al, 2018;Dev Bhurtun et al, 2021). Various factors also determine their coping strategies (Bodys-Cupak et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the majority of medical rescuers analysed admit that extreme stress during rescue missions does not overcome their possibilities of adaptation and does not cause a reduction in their readiness to participate in future rescue missions [6]. This problematic issue is developed intensively, which is expressed by the currently conducted research on the strategies of coping with stress among groups of medical students, while also during the first clinical practice [7]. There are reports that illustrate the intricate relations between the patient-related stressors and coping strategies in baccalaureate nursing students during clinical practice [8].…”
Section: Introductionmentioning
confidence: 99%